2004
DOI: 10.1097/01.mlr.0000135828.95415.b1
|View full text |Cite
|
Sign up to set email alerts
|

Does Hospitalization Impact Survival After Lower Respiratory Infection in Nursing Home Residents?

Abstract: After controlling for illness severity and propensity for hospitalization, hospital treatment is not associated with either increased or decreased risk for mortality for nursing home residents with LRIs. For residents with low and medium mortality risk, nursing home treatment is likely to be safe and less costly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 32 publications
4
47
2
2
Order By: Relevance
“…Previous analysis of Missouri LRI Study data found no difference in 1-month mortality between residents fi rst treated in the nursing home or the hospital, after adjusting for illness severity and probability of hospitalization. 40 The study' s main limitation is the universal problem with observational studies-we were unable to assure adequate control for confounding. Across levels of illness severity and between the 2 countries, residents received very different therapies, making it diffi cult to compare outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analysis of Missouri LRI Study data found no difference in 1-month mortality between residents fi rst treated in the nursing home or the hospital, after adjusting for illness severity and probability of hospitalization. 40 The study' s main limitation is the universal problem with observational studies-we were unable to assure adequate control for confounding. Across levels of illness severity and between the 2 countries, residents received very different therapies, making it diffi cult to compare outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A potential reason for this could be that those in later stages of AD forgo hospitalization in lieu of home care or care provided at the nursing home. Research suggests that certain common acute conditions, such as pneumonia, can be treated with the same efficacy and at reduced costs in the nursing home than in the hospital [29,30]. The potential benefits of hospitalization may outweigh its burdens for patient's whose primary goal of care remains life prolongation, but comfort if often considered the priority of care in the final stages of AD [31].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers examined associations between treatment and outcome in frequently occurring treatment dilemmas, such as withholding antibiotics in patients with fever [30] or pneumonia [31], intake problems [32], and in hospitalization decisions [70,71].…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%